THE EFFECT OF ENTREPRENEURSHIP EDUCATION AND FAMILY ENVIRONMENT ON INTERESTS ENTREPRENEURSHIP IN STUDENT OF THE FACULTY OF ECONOMICS, UNIVERSITY OF NGURAH RAI IN DENPASAR - Purnamawati, Ni Kadek; Adiandari, Ade Maharini; Amrita, Nyoman Dwika Ayu; Perdanawati, Luh Putu Virra Indah (ADI Journal on Recent Innovation, 2020)
This study aims to determine the effect of entrepreneurship education and family environment partially and simultaneously on the interest in entrepreneur in student of the Faculty of Economics, University of Ngurah Rai in Denpasar. The number of samples is determined by the Probability Sampling technique using the Simple Random Sampling method of 75 students in the sixth semester of the Faculty of Economics, University of Ngurah Rai in Denpasar. Analyzed by classical assumption, multiple linear regression analys, determination analys, simultaneous significant test (F-test) and partial significant test (T-test). The results showed that there was a positive and significant influence partially or simultaneously between entrepreneur education and the family environment towards the interest in entrepreneurship in students of the Faculty of Economics, University of Ngurah Rai in Denpasar.